Moving Citational Justice from the Print Age into the Artificial Intelligence Age - Basaraba, Nicole (KULA)

(untitled) (University of Victoria Libraries, 2026)
This paper examines the evolution of academic citation practices from print into digital contexts. While standardised citation styles only became widespread in the mid-twentieth century, the digital era has raised new questions about credibility, authority, and the recognition of diverse sources. Contemporary shifts—including the rise of alternative scholarly outputs, decolonisation movements, and artificial intelligence—have highlighted various forms of citational injustice and misbehaviours, prompting corrective interventions. While these approaches represent progress, they often remain narrowly focused and lack a broader theoretical orientation capable of driving multi-level systemic change in the context of developing technologies such as artificial intelligence, which are being used by some scholars as research tools. This paper serves as a foundation for developing a new citational justice framework in future research. Working towards improved citational justice is not only about recognising, acknowledging, and combating citational and epistemic injustice but also about rethinking the academic culture of research communications in digital citation contexts. Collective action and sustained structural transformation are needed to reshape digital citation practices towards more equitable and transparent paradigms of knowledge production in the rapidly changing digital publishing landscape.